A Stress Level Monitoring System for Rescue Teams During Search and Rescue Operations Based on Electroencephalography - dedy hariyadi; adhi dharma wibawa; wirawan wirawan (JAREE (Journal on Advanced Research in Electrical Engineering), 2025)
Search and Rescue (SAR) officers work in high-risk conditions that require physical and mental resilience. Prolonged stress can affect the performance and success of SAR operations. This study evaluates the effectiveness of Electroencephalography (EEG) coherence analysis as a method for monitoring stress in SAR personnel. Using the OpenBCI EEG device and electrodes in the F3 and F4 areas, the brain activity of SAR personnel was recorded in two conditions, office activity (baseline) and rescue operations (SAR condition). The data collection for this research involved the same participants in both baseline and SAR operation conditions, resulting in 30 raw EEG data for further analysis. Data collection on operational conditions was carried out while the rescue officers conducted a search and rescue operation for a capsized boat in the Bengawan Solo River, Ngadirejo Village, Tuban Regency. Data analyzed based on coherence values obtained through the Power Spectral Density (PSD) features of alpha, beta, and gamma sub-band to detect changes related to stress levels. The results showed an increase in coherence in the alpha sub-band by 85.5%, beta sub-band by 92.9%, and gamma sub-band by up to 94.9% during moderate stress conditions, reflecting increased attention, alertness, and intensive information processing required in emergency situations. These findings indicate that EEG coherence analysis can be an effective tool for monitoring stress in SAR personnel in real-time.